The fragility of consensus: ideological polarization in post-Pinochet Chile - Lindh, Jaime; Fábrega, Jorge; González, Jorge (Revista de Ciencia Política, 2019)
This article presents evidence of political, socioeconomic and generational polarization among the Chilean population between 1990 and 2017. Using data from the Public Opinion Survey of the CEP, the ideology of the individuals is estimated indirectly using the methodology developed by Poole (1998). The main findings are the following: (i) in 1993, adherents and opponents of the current government initiated a process of ideological distancing that was consolidated in mid-2008; (ii) the ideological distance between high and low socioeconomic levels began to increase from 2005 onwards; and finally, (iii) the generation born before 1955 began to distance itself ideologically from the one born after 1980, since 2011.